Two mid-sixteenth-century Cecilian parody masses - Henriques, Luís (2021)
Musical celebrations of the feast of St Cecilia were common in Europe since the fifteenth century and throughout the sixteenth century. Of the many composers who wrote music for this festivity we find four mid-sixteenth-century compositions by French composers. Two motets Cantantibus orgnis and Cecilia virgo gloriosa - by Pierre Certon which served as models for two parody masses (with same titles as the models) by Pierre Clereau. This text examines both models and the respective masses with a glimpse at the parody procedures used by Clereau in his works.